Multi-active site nitrogen-containing heterocyclic covalent organic framework material and preparation method and application thereof

By designing and synthesizing nitrogen-containing heterocyclic COF materials with multi-active sites and the positive electrode materials used in aqueous zinc ion batteries, the problems of insufficient discharge capacity and cycle stability of existing materials are solved, and high-performance and low-cost battery materials are achieved.

CN116925355BActive Publication Date: 2025-03-14CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310900555.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-03-14
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

The discharge capacity and long cycle stability of the existing water-based zinc-ion battery positive electrode materials still need to be improved, and the raw materials used are expensive and the preparation process is complicated.

Method used

A nitrogen-containing heterocyclic covalent organic framework material (COF) with multi-active sites was designed and synthesized, and the HTPA-COF and HTMD-COF materials were prepared by dehydration and condensation reaction of hexazabenzophenylaxencarboxylic trianhydride and p-phenylenediamine or m-phenylenediamine, and used as a positive electrode material in aqueous zinc ion batteries.

Benefits of technology

The first discharge capacity value is better than many reported organic electrode materials under small current density, with high reversibility and long cycle stability, and the raw materials used are cheap and the preparation process is simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116925355B_ABST
    Figure CN116925355B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of synthesis of electrode materials, and particularly relates to a type of nitrogen-containing heterocyclic covalent organic framework (COF) material with multiple active sites, and its preparation method and application. The preparation steps are as follows: under the protection of inert gas, dehydration condensation reaction is carried out by hexaazatriphenylene hexacarboxylic acid trianhydride and p-phenylenediamine or m-phenylenediamine. After the reaction is completed, heating is stopped, and appropriate amounts of deionized water and acetone are added for washing, and suction filtration is performed to synthesize a nitrogen-containing heterocyclic COF with multiple active sites. This type of COF is used to prepare positive electrode materials for aqueous zinc ion batteries, which not only have good discharge capacity and long-term cycle stability, but also the assembled flexible battery has a higher volume energy density, good flexibility and excellent mechanical toughness against repeated bending, showing its broad application prospects in the field of wearable electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of synthesis of electrode materials, and in particular relates to a type of multi-active site nitrogen-containing heterocyclic covalent organic framework material (COF) and a preparation method thereof and application thereof in preparing positive electrode materials for aqueous zinc ion batteries. Technical Background

[0002] With the gradual depletion of energy resources and ecological pollution, the development of new energy storage devices has attracted wide attention. Therefore, the development of rechargeable batteries with excellent rate performance, high safety, environmental protection and low cost has become an important topic.

[0003] The redox potential of zinc anode is higher than that of other metal anodes (-0.76Vvs. standard hydrogen electrode), and it has excellent stability in water phase, which is suitable for aqueous battery system. Moreover, replacing traditional organic electrolytes with aqueous electrolytes can greatly reduce environmental pollution and cost. Combining the advantages of safety, abundant zinc sources and environmental friendliness, it is of great significance to develop high-performance large-scale energy storage aqueous zinc ion batteries (AZIBs).

[0004] In recent years, the research on AZIBs has mainly focused on the research and development of cathode materials. In the process of ion storage, researchers have been looking for cathode materials with excellent stable structure and high capacity. At present, people mainly develop electrode materials with high energy density and high power density by regulating the morphological structure, but most of them are inorganic materials, which may bring serious problems such as high recycling cost and environmental pollution (ChemElectroChem, 2020, 7(19): 3905-3926.). In recent years, organic compounds have become an attractive cathode material for zinc batteries due to their low toxicity, large theoretical capacity, structural diversity, controllable synthesis, low cost and strong sustainability. Although organic electrode materials have many advantages, their development and research still encounter some problems (J.Mater.Chem.A, 2016, 4(29): 11179-11202.). For example, small organic molecules are easily soluble in electrolyte solutions and have poor cycle stability.

[0005] Covalent organic framework (COF) is an environmentally friendly organic electrode material with adjustable structure. It has attracted extensive attention in recent years and has become a promising organic electrode material for rechargeable batteries. Because of its large specific surface area, adjustable pore size, structural predictability and stability, and the two-dimensional covalent organic framework material layers are connected to each other in a π-π stacking manner, Zn 2+ Easy to transport. In 2019, Abdul's research group reported that a covalent organic framework COF (HqTp) with multiple nucleophilic centers was used as a positive electrode material for aqueous zinc-ion batteries. HqTp is 125 mAg -1 The current shows 276mAhg-1 Excellent discharge capacity (Chem. Sci., 2019, 10, 8889-8894). In 2021, Wang et al. reported a strategy to improve the electrochemical performance of the positive electrode in AZIB by introducing quinone groups into COF based on 1,4,5,8,9,12-hexaazatriphenylene. Electrochemical characterization showed that the introduction of quinone groups in COF significantly improved the electrochemical performance of Zn 2+ For H + The storage capacity of AZIB is improved and the average discharge potential of AZIB is increased (Adv. Mater., 2021, 33, 2103617). Therefore, the design and synthesis of COFs with multiple active sites provides a feasibility for obtaining more high-performance and stable organic electrode materials.

[0006] Patent CN114976297A discloses a type of COF material prepared by dehydration condensation reaction of hexaazanaphthylidene triphenylene hexacarboxylic acid trianhydride with 2,6-diaminoanthraquinone or N,N'-diamino-1,4,5,8-naphthalenetetraimide. The raw materials 2,6-diaminoanthraquinone and N,N'-diamino-1,4,5,8-naphthalenetetraimide used in the patent are expensive, and the discharge capacity and long cycle stability of the prepared polycarbonyl hexaazanaphthylidene derivative COF material still need to be improved. Summary of the invention

[0007] The object of the present invention is to provide a type of nitrogen-containing heterocyclic covalent organic framework material (COF) with multiple active sites, a preparation method thereof, and an application thereof in preparing positive electrode materials for aqueous zinc ion batteries.

[0008] The present invention starts from the structural design of COFs, introduces multiple redox active sites, and synthesizes organic electrode materials. The present invention proves an effective strategy for designing COF structures at the molecular level, which provides a new direction for improving electrochemical zinc storage performance.

[0009] The structural formula of the nitrogen-containing heterocyclic COF material with multiple active sites is as follows:

[0010]

[0011]

[0012] Among them, R is The nitrogen-containing heterocyclic COF material with multiple active sites is labeled as HTPA-COF;

[0013] R is The nitrogen-containing heterocyclic COF material with multiple active sites is marked as HTMD-COF.

[0014] The present invention also provides a method for synthesizing the nitrogen-containing heterocyclic compound type COF with multiple active sites: hexaazatriphenylene hexacarboxylic acid trianhydride is subjected to a dehydration condensation reaction with p-phenylenediamine or m-phenylenediamine to prepare a nitrogen-containing heterocyclic COF with multiple active sites.

[0015] The specific steps are as follows:

[0016] (1) Under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride and an organic solvent are added to a reactor, and p-phenylenediamine or m-phenylenediamine is completely dissolved and evenly dispersed. Then, the temperature is raised to reflux under stirring conditions to carry out a dehydration condensation reaction.

[0017] The synthesis reaction equation involved in the present invention is as follows:

[0018]

[0019] Wherein, the molar ratio of hexaazatriphenylene hexacarboxylic acid trianhydride to p-phenylenediamine or m-phenylenediamine is 1:1.5-1.6.

[0020] The organic solvent is 1-methyl-2-pyrrolidone (NMP) or N,N-dimethylformamide (DMF).

[0021] The dehydration condensation reaction time is 36-48 hours.

[0022] The inert gas is nitrogen or argon.

[0023] (2) After the reaction is completed, the heating is stopped, the product is cooled to room temperature and then filtered, washed with deionized water and acetone for 2-3 times, and vacuum dried to obtain the nitrogen-containing heterocyclic COF with multiple active sites.

[0024] The use of the nitrogen-containing heterocyclic COF with multiple active sites in the preparation of positive electrode materials for aqueous zinc ion batteries. Preferably, the nitrogen-containing heterocyclic COF with multiple active sites accounts for 30% of the positive electrode material.

[0025] Preferably, the nitrogen-containing heterocyclic COF material with multiple active sites used for the positive electrode material of aqueous zinc ion batteries is HTMD-COF.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] Compared with the disclosed patent: CN114976297A-polycarbonyl hexaazanaphthalene derivative type COF material and its preparation method and application, the raw materials p-phenylenediamine (PPDA) or m-phenylenediamine (MPD) used in this patent are cheaper and more abundant than the raw materials 2,6-diaminoanthraquinone and N,N'-diamino-1,4,5,8-naphthalenetetraimide used in the above patents; the steps for synthesizing the corresponding COF materials in this patent are simpler, and the prepared flexible battery also has better long-cycle stability. More importantly, the COF electrode in this patent has a better first discharge capacity value at a low current density than many reported aqueous zinc ion battery systems with organic electrode materials as the positive electrode, and has high reversibility. In addition, this patent demonstrates the effect of flexible batteries lighting up LED lights, which provides a more intuitive explanation of the practical application of batteries. In summary, the flexible zinc battery constructed by the COF electrode in this patent is expected to be used in wearable electronic products, providing a feasible new idea for the development of organic electrode materials.

[0028] The nitrogen-containing heterocyclic COF with multiple active sites of the present invention adopts a heating reflux method, which is relatively simple to operate and has good reproducibility. Due to the multiple redox active sites and insolubility in aqueous electrolytes, when HTPA-COF and HTMD-COF are used as positive electrode materials for aqueous zinc batteries, they exhibit excellent cycle stability and high specific capacity. In addition, the nitrogen-containing heterocyclic COF material with multiple active sites has a two-dimensional polymerized covalent framework network structure, which effectively solves the problem of dissolution of discharge products in electrolytes and greatly improves the long-cycle stability of Zn / / HTPA-COF and Zn / / HTMD-COF battery systems. And the flexible Zn / / HTPA-COF and Zn / / HTMD-COF batteries have high energy density, power density and excellent bending and folding characteristics, showing great potential in the application field of wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The infrared spectra of nitrogen-containing heterocyclic HTPA-COF with multiple active sites and its reactants HHCT and PPDA;

[0030] Figure 2 The powder X-ray diffraction spectra of nitrogen-containing heterocyclic HTPA-COF with multiple active sites and its reactants HHCT and PPDA;

[0031] Figure 3 This is the solid-state nuclear magnetic resonance H spectrum of the nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0032] Figure 4 This is the solid-state NMR C spectrum of the nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0033] Figure 5 This is a scanning electron microscopy image of the nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0034] Figure 6 This is the Raman spectrum of nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0035] Figure 7 This is the thermogravimetric curve of nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0036] Figure 8 The adsorption-desorption curve and pore size distribution curve of nitrogen-containing heterocyclic HTPA-COF with multiple active sites (inset);

[0037] Fig. 9 The charge and discharge diagram of the nitrogen-containing heterocyclic HTPA-COF button battery with multiple active sites under different load ratios;

[0038] Fig.10 The stability diagram of nitrogen-containing heterocyclic HTPA-COF button cells with multiple active sites at different load ratios;

[0039] Fig.11 The cyclic voltammogram of the nitrogen-containing heterocyclic HTPA-COF button cell with multiple active sites at the same scan rate;

[0040] Fig.12 The figure shows the kinetic properties of nitrogen-containing heterocyclic HTPA-COF button cells with multiple active sites at different scan rates;

[0041] Fig.13 The charge and discharge diagram of the nitrogen-containing heterocyclic HTPA-COF button cell with multiple active sites at different current densities;

[0042] Fig.14 The rate diagram of nitrogen-containing heterocyclic HTPA-COF button cell with multiple active sites at different current densities;

[0043] Fig.15 The cycling stability diagram of nitrogen-containing heterocyclic HTPA-COF button cells with multiple active sites at the same current density;

[0044] Fig.16 This is the dissolution diagram of nitrogen-containing heterocyclic HTPA-COF with multiple active sites;

[0045] Fig.17 The energy density and power density diagram of the nitrogen-containing heterocyclic HTPA-COF button cell with multiple active sites;

[0046] Fig.18 The constant current charge and discharge diagram of the nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites at different current densities;

[0047] Fig.19 This is the rate diagram of the nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites at different current densities;

[0048] Fig. 20 This is a long cycle stability diagram of nitrogen-containing heterocyclic HTPA-COF flexible batteries with multiple active sites;

[0049] Fig.21 The volume energy density and power density diagram of the nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites;

[0050] Fig. 22 The cycling stability diagram of the nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites at different folding angles;

[0051] Fig.23 The charge and discharge diagram of the nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites at different folding angles;

[0052] Fig.24 Pictures of a nitrogen-containing heterocyclic HTPA-COF flexible battery with multiple active sites lighting up a small light bulb in different states;

[0053] Fig.25 The infrared spectra of nitrogen-containing heterocyclic HTMD-COF with multiple active sites and its reactants HHCT and MPD;

[0054] Fig.26 The powder X-ray diffraction spectra of nitrogen-containing heterocyclic HTMD-COF with multiple active sites and its reactants HHCT and MPD;

[0055] Fig. 27 The solid-state NMR C spectrum of nitrogen-containing heterocyclic HTMD-COF with multiple active sites;

[0056] Fig.28 This is a scanning electron microscopy image of the nitrogen-containing heterocyclic HTMD-COF with multiple active sites;

[0057] Fig.29 This is the Raman spectrum of nitrogen-containing heterocyclic HTMD-COF with multiple active sites;

[0058] Fig.30 The thermogravimetric curve of nitrogen-containing heterocyclic HTMD-COF with multiple active sites;

[0059] Fig.31 The adsorption-desorption curve and pore size distribution curve of nitrogen-containing heterocyclic HTMD-COF with multiple active sites (inset);

[0060] Fig.32 The charge and discharge diagram of the nitrogen-containing heterocyclic HTMD-COF button cell with multiple active sites under different load ratios;

[0061] Fig.33 The stability diagram of nitrogen-containing heterocyclic HTMD-COF button cells with multiple active sites at different load ratios;

[0062] Fig.34 The cyclic voltammogram of the nitrogen-containing heterocyclic HTMD-COF button cell with multiple active sites at the same scan rate;

[0063] Fig.35 The kinetic properties of nitrogen-containing heterocyclic HTMD-COF button cells with multiple active sites at different scan rates are shown in the figure.

[0064] Fig.36 The charge and discharge diagram of the nitrogen-containing heterocyclic HTMD-COF button cell with multiple active sites at different current densities;

[0065] Fig.37 The rate diagram of nitrogen-containing heterocyclic HTMD-COF button cell with multiple active sites at different current densities;

[0066] Fig.38 The cycling stability diagram of nitrogen-containing heterocyclic HTMD-COF button cells with multiple active sites at the same current density;

[0067] Fig.39 This is the dissolution diagram of nitrogen-containing heterocyclic HTMD-COF with multiple active sites;

[0068] Fig.40 The energy density and power density diagram of the nitrogen-containing heterocyclic HTMD-COF button cell with multiple active sites;

[0069] Fig.41 The constant current charge and discharge diagram of the nitrogen-containing heterocyclic HTMD-COF flexible battery with multiple active sites at different current densities;

[0070] Fig.42 The rate diagram of nitrogen-containing heterocyclic HTMD-COF flexible battery with multiple active sites at different current densities;

[0071] Fig.43This is a long cycle stability diagram of nitrogen-containing heterocyclic HTMD-COF flexible batteries with multiple active sites;

[0072] Fig.44 The volume energy density and power density of the nitrogen-containing heterocyclic HTMD-COF flexible battery with multiple active sites are shown in Figure 2.

[0073] Fig.45 The cycling stability diagram of nitrogen-containing heterocyclic HTMD-COF flexible batteries with multiple active sites at different folding angles;

[0074] Fig.46 The charge and discharge diagrams of the nitrogen-containing heterocyclic HTMD-COF flexible battery with multiple active sites at different folding angles;

[0075] Fig.47 Pictures of the nitrogen-containing heterocyclic HTMD-COF flexible battery with multiple active sites lighting up a small light bulb under different conditions. Specific implementation methods

[0076] The present invention will be further described below by means of specific examples.

[0077] Example 1

[0078] 90 mL of N, N-dimethylformamide (DMF) was added to a 250 mL three-necked flask. After nitrogen was passed for 30 minutes, hexaazatriphenylene hexacarboxylic acid trianhydride (HHCT) (0.4442 g, 1 mmol) and p-phenylenediamine (PPDA) (0.1622 g, 1.5 mmol) were accurately weighed as reaction raw materials, and placed in the three-necked flask. The reaction raw materials were dissolved by magnetic stirring. Heat until reflux and reflux for 36 hours. After the reaction was completed, cool and filter, wash the filter cake with appropriate amount of deionized water and acetone, and vacuum dry at 80 ° C overnight to finally obtain COF material HTPA-COF with a yield of 67%.

[0079] Figure 1 is the infrared spectra of HTPA-COF and its reactants HHCT and PPDA; Figure 2 is the powder X-ray diffraction spectrum of HTPA-COF and its reactants HHCT and PPDA; Figure 3 is the solid state H NMR spectrum of HTPA-COF; Figure 4 is the solid state carbon NMR spectrum of HTPA-COF; Figure 5 is the scanning electron microscope image of HTPA-COF; Figure 6 is the Raman spectrum of HTPA-COF; Figure 7 It is the thermogravimetric curve of HTPA-COF; Figure 8The adsorption-desorption curve and pore size distribution curve of HTPA-COF (inset). It can be seen that the HTPA-COF material is composed of spherical particles with a diameter of hundreds of nanometers, with a medium defect level and high thermal stability, and has a certain amount of pores, which is conducive to Zn 2+ conductivity, making it suitable as an electrode material.

[0080] The active material of HTPA-COF as an electrode material is mixed and ground according to different mass ratios of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%, or 60%: 30%: 10%, or 80%: 10%: 10%, then a diffusant (NMP) is added dropwise and ground, and the mixture is coated on a current collector titanium mesh or a stainless steel mesh, and vacuum dried at 80°C to form an electrode sheet, which is used as a positive electrode, a zinc sheet as a negative electrode, and a Whatman GB / F as a separator. 2 mol·L -1 ZnSO4 was dissolved in distilled water as the electrolyte, assembled into button cells, and their electrochemical properties were investigated. Fig. 9 This is the charge and discharge diagram of button batteries under different load ratios; Fig.10 This is a stability diagram of button batteries under different load ratios; it can be seen that when the active material accounts for 30%, the battery capacity is higher.

[0081] The active material of HTPA-COF as the electrode material is mixed and ground according to the mass ratio of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%, and then a dispersant (NMP) is added and ground, and then coated on a current collector titanium mesh or a stainless steel mesh, and vacuum dried at 80°C to form an electrode sheet, which is used as the positive electrode, the zinc sheet as the negative electrode, and Whatman GB / F as the separator. 2 mol·L -1 ZnSO4 was dissolved in distilled water as the electrolyte, assembled into button batteries and flexible batteries, and their electrochemical properties were investigated.

[0082] Fig.11 For button cells at 0.5mV s -1 Cyclic voltammogram at scan rate; Fig.12 The figure shows the kinetic properties of button cells at different scan rates; Fig.13 This is the charge and discharge diagram of button battery at different current densities; Fig.14 This is the rate diagram of button cell at different current densities; Fig.15 For button cells at 2Ag -1 Cycling stability diagram at different current densities; Fig.16 This is the dissolution test diagram of HTPA-COF; Fig.17 Energy density and power density diagram of button cell.

[0083] Fig.18This is the constant current charge and discharge diagram of the flexible battery at different current densities; Fig.19 This is the rate diagram of the flexible battery at different current densities; Fig. 20 This is the long cycle stability diagram of the flexible battery; Fig.21 The volume energy density and power density diagram of the flexible battery; Fig. 22 This is the cycle stability diagram of the flexible battery at different folding angles; Fig.23 This is the charge and discharge diagram of the flexible battery at different folding angles. Fig.24 Pictures of flexible batteries lighting up small light bulbs in different states.

[0084] Example 2

[0085] The experimental method is the same as that of Example 1, except that the raw material p-phenylenediamine (PPDA) is replaced by m-phenylenediamine (MPD), and finally the COF material HTMD-COF is obtained with a yield of 76%.

[0086] Fig.25 is the infrared spectra of HTMD-COF and its reactants HHCT and MPD; Fig.26 is the powder X-ray diffraction spectrum of HTMD-COF and its reactants HHCT and MPD; Fig. 27 is the solid state carbon NMR spectrum of HTMD-COF; Fig.28 is the scanning electron microscope image of HTMD-COF; Fig.29 is the Raman spectrum of HTMD-COF; Fig.30 is the thermogravimetric curve of HTMD-COF; Fig.31 The adsorption-desorption curve and pore size distribution curve of HTMD-COF (inset). It can be seen that the HTMD-COF material is composed of irregular nanoparticles; it has a medium defect level and high thermal stability, which is conducive to the electrode to obtain a good cycle efficiency; and it has a certain amount of pores, which is conducive to Zn 2+ conductivity, and is a suitable electrode material.

[0087] The active material of HTMD-COF as an electrode material is mixed and ground according to different mass ratios of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%, or 60%: 30%: 10%, or 80%: 10%: 10%, then a diffusant (NMP) is added dropwise and ground, and the mixture is coated on a current collector titanium mesh or a stainless steel mesh, and vacuum dried at 80°C to form an electrode sheet, which is used as a positive electrode, a zinc sheet as a negative electrode, and a Whatman GB / F as a separator. 2 mol·L -1 ZnSO4 was dissolved in distilled water as the electrolyte, assembled into button cells, and their electrochemical properties were investigated. Fig.32 This is the charge and discharge diagram of button batteries under different load ratios; Fig.33This is a stability diagram of button batteries under different load ratios; it can be seen that the active material accounts for 30%, and the battery capacity is higher.

[0088] The active material of HTMD-COF as the electrode material was mixed and ground according to the mass ratio of active material: Ketjen black: binder (PVDF) = 30%: 60%: 10%, and then a dispersant (NMP) was added and ground, and then coated on a current collector titanium mesh or a stainless steel mesh, and vacuum dried at 80°C to form an electrode sheet. The electrode sheet was used as the positive electrode, the zinc sheet was used as the negative electrode, and Whatman GB / F was used as the separator. 2 mol·L -1 ZnSO4 was dissolved in distilled water as the electrolyte, assembled into button batteries and flexible batteries, and their electrochemical properties were investigated.

[0089] Fig.34 For button cells at 0.5mV s -1 Cyclic voltammogram at scan rate; Fig.35 The figure shows the study of the kinetic properties of button cells at different scan rates; Fig.36 This is the charge and discharge diagram of button battery at different current densities; Fig.37 This is the rate diagram of the button electrode at different current densities; Fig.38 For button cells at 2Ag -1 Cycling stability diagram at different current densities; Fig.39 This is the dissolution test diagram of HTMD-COF; Fig.40 Energy density and power density diagram for button cells;

[0090] Fig.41 This is the constant current charge and discharge diagram of the flexible battery at different current densities; Fig.42 This is the rate diagram of the flexible battery at different current densities; Fig.43 This is the long cycle stability diagram of the flexible battery; Fig.44 The volume energy density and power density diagram of the flexible battery; Fig.45 This is the cycle stability diagram of the flexible battery at different folding angles; Fig.46 This is the charge and discharge diagram of the flexible battery at different folding angles. Fig.47 Pictures of flexible batteries lighting up small light bulbs in different states.

Claims

1. A nitrogen-containing heterocyclic covalent organic framework material with multiple active sites, characterized in that: The nitrogen-containing heterocyclic covalent organic framework material with multiple active sites is HTPA-COF or HTMD-COF; the structural formula of the HTPA-COF is as follows, wherein R= : The structural formula of the HTMD-COF is shown below, wherein R= ; 。 2. A method for preparing a nitrogen-containing heterocyclic covalent organic framework material having multiple active sites as claimed in claim 1, characterized in that: The method comprises the following steps: heating hexaazatriphenylene hexacarboxylic acid trianhydride and p-phenylenediamine or m-phenylenediamine to reflux for dehydration condensation reaction to prepare a nitrogen-containing heterocyclic covalent organic framework material with multiple active sites.

3. The method for preparing the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites according to claim 2, characterized in that: The dehydration condensation reaction method is: under the protection of inert gas, hexaazatriphenylene hexacarboxylic acid trianhydride and organic solvent, as well as p-phenylenediamine or m-phenylenediamine are added into a reactor, and after being completely dissolved and evenly dispersed, the temperature is raised to reflux under stirring conditions to carry out the dehydration condensation reaction.

4. The method for preparing the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites according to claim 2, characterized in that: After the dehydration condensation reaction is completed, the heating is stopped, the product is cooled to room temperature and then filtered, washed with deionized water and acetone for 2-3 times in sequence, and vacuum dried to obtain a nitrogen-containing heterocyclic COF with multiple active sites.

5. The method for preparing the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites according to claim 2, characterized in that: The molar ratio of the hexaazatriphenylene hexacarboxylic acid trianhydride to p-phenylenediamine or m-phenylenediamine is 1:1.5-1:

6.

6. The method for preparing the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites according to claim 3, characterized in that: The organic solvent is 1-methyl-2-pyrrolidone or N,N-dimethylformamide.

7. The method for preparing a nitrogen-containing heterocyclic covalent organic framework material with multiple active sites according to claim 3, characterized in that: The dehydration condensation reaction time is 36-48 hours.

8. The method for preparing a nitrogen-containing heterocyclic compound-type covalent organic framework material having multiple active sites according to claim 3, characterized in that: The inert gas is nitrogen or argon.

9. An application of the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites as claimed in claim 1, characterized in that: Application of the nitrogen-containing heterocyclic covalent organic framework material with multiple active sites in the preparation of positive electrode materials for aqueous zinc ion batteries.

Citation Information

Patent Citations

  • Polycarbonyl hexaaza-naphthalene derivative type COF material as well as preparation method and application thereof

    CN114976297A

  • High-stability zinc-iodine battery positive electrode composite material as well as preparation method and application thereof

    CN113036144A

  • Polyimide containing hexaazabenzophenanthrene structure and preparation method thereof

    CN114196014A